Foot gangrene following Tagraxofusp treatment for blastic plasmacytoid dendritic cell neoplasm: Case report. Issue 4 (4th August 2022) - Sibai, Jad; Chen, RuiQi; Nabhani, Ibrahim Al; Perusini, Maria Agustina; Sibai, Hassan
Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and aggressive hematologic malignancy. It is associated with poor prognosis and heterogenous presentation. The CD123‐directed cytotoxin, Tagraxofusp, is a targeted therapy for BPDCN. Here, we report an 81‐year‐old female diagnosed with BPDCN. The patient was treated with Tagraxofusp and underwent a remarkably long remission (>20 months) without stem‐cell transplantation. She, however, experienced blue toe syndrome and left foot gangrene. We postulate that these previously unreported side effects were caused by microembolization. Characterization of the incidence of thrombo‐ and microembolizations in such a context, as well as prophylactic management options, are warranted.